Analytical and molecular dynamical investigations of the influence of molecular vibrations upon the (e, 2e) electron momentum distributions of furan. (August 2015) - Morini, F; Deleuze, M S; Watanabe, N; Takahashi, M
Synopsis: The role of molecular vibrations has been theoretically investigated in the electronic ground state on the (e, 2e) valence orbital momentum profiles of furan by means of two complementary approaches. The first one relies upon the principles of Born-Oppenheimer Molecular Dynamics (BOMD), whereas the second one, referred as Harmonic Analytical Quantum Mechanical (HAQM) approach, includes on quantum-mechanical